Overprescribing and rational therapeutics: Barriers to change and opportunities to improve. Issue 1 (14th April 2020) - Bennett, Frances; Ferner, Robin; Sofat, Reecha
Abstract : There is increasing national and international interest in overprescribing and polypharmacy, and the burden that the inappropriate use of multiple medicines can place on individual patients and on society as a whole. This paper explores the challenges faced by prescribers and pharmacists wishing to reduce polypharmacy, including the uncertainties about the risks and benefits of continuing or stopping individual drugs. We discuss the factors influencing us to prescribe—which may lead to overprescribing—including the increasing number of guidelines, perceived patient pressure and advertising. We offer a critical appraisal of the tools currently available to clinicians and pharmacists aiming to rationalise medicines, and finally a systems‐wide approach to improving overprescribing and problematic polypharmacy.